I405V polymorphism of CETP gene and lipid profile in women with endometriosis. (July 2013) - Sahmani, Mehdi; Ghaleh, Talaat Dabbaghi; Darabi, Maryam; Darabi, Masoud; Rashvand, Zahra; Najafipour, Reza
Abstract Genetic factors have an important role in the pathophysiology of endometriosis. In addition, abnormalities in lipid profile and intrinsic inflammatory status are associated with disease progression. The purpose of this study was to evaluate the effect of the I405V polymorphism of cholesteryl ester transfer protein (CETP) gene and lipid profile with the risk of endometriosis in women. Ninety-seven women with laparoscopy-diagnosed endometriosis were recruited for this study, and 107 patients with no evidence of endometriosis confirmed by laparoscopy served as controls. Samples were analyzed for polymorphism of the CETP gene using polymerase chain reaction–restriction fragment length polymorphism-based methods. After adjustment for body mass index, high-density lipoprotein-C and low-density lipoprotein-C, the risk of endometriosis in patients with normal genotype homozygous was more of the rare allele (p < 0.001, odds ratio = 0.21, 95% confidence interval = 0.09–0.45). Our results suggest that I405V polymorphism of CETP gene plays an important role as independent factor in the risk of endometriosis in women.